2013
DOI: 10.3390/en6126274
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Defining Electricity Demand in Energy Simulations Referred to the Italian Context

Abstract: Electricity consumption in Europe is constantly increasing, despite the fact that in recent years, huge efforts in terms of programs and regulations have been made towards energy demand reduction and energy systems improvement. Since the electricity demand affects both the operation of the supply and distribution plants and the thermal loads of buildings, the importance of providing a proper definition of demand profiles is evident. The main aim of the paper is to provide a set of standard electricity profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The core of the method is a more accurate tool to calculate the internal gains from lighting: this means that the contribution to internal gains from appliances and occupancy is assumed constant on the basis of literature reference values • applying the proposed calculation procedure to a real casestudy (the building hosting the Department of Energy at the Politecnico di Torino, Italy) and comparing the EP gl to the value which would be obtained through the assumption of 6 W/m 2 for all internal gains, as prescribed by the technical standards • estimating how the considered site influences the difference between the two approaches, repeating the calculations for a It is worth stressing that the procedure which is proposed in this paper refers to the energy certification, based on the standard use of a building, and not to the real utilization profile (HVAC and lighting systems, appliances, internal gains, regulation systems etc. ), like [13] did in their study. Internal loads and the electricity demand in real buildings depend on a high number of aspects.…”
Section: Objective Of the Studymentioning
confidence: 93%
See 2 more Smart Citations
“…The core of the method is a more accurate tool to calculate the internal gains from lighting: this means that the contribution to internal gains from appliances and occupancy is assumed constant on the basis of literature reference values • applying the proposed calculation procedure to a real casestudy (the building hosting the Department of Energy at the Politecnico di Torino, Italy) and comparing the EP gl to the value which would be obtained through the assumption of 6 W/m 2 for all internal gains, as prescribed by the technical standards • estimating how the considered site influences the difference between the two approaches, repeating the calculations for a It is worth stressing that the procedure which is proposed in this paper refers to the energy certification, based on the standard use of a building, and not to the real utilization profile (HVAC and lighting systems, appliances, internal gains, regulation systems etc. ), like [13] did in their study. Internal loads and the electricity demand in real buildings depend on a high number of aspects.…”
Section: Objective Of the Studymentioning
confidence: 93%
“…In [13], they carried out a study on the energy and lighting performances for energy-efficient fluorescent lamps associated with electronic ballasts and high frequency photoelectric dimming controls installed in a school building. They showed that T5 fluorescent lamps associated with the electronic ballasts installed to replace the existing T8 light fittings with conventional ballasts lead to a 28% reduction in energy expenditure for electric lighting in a workshop room.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…shows deviations in annual yields lower than 3.5% and accordance with the generated electricity during the whole period under review. In addition to the PV generation profile, simulation of load demand is required, but the consumption in a household varies significantly dependent on environmental conditions and especially on consumer behavior, existing equipment and its home application [46]. These typical fluctuations are only observable at high time resolutions.…”
Section: Input Datamentioning
confidence: 99%
“…The methodology illustrated in the Section 2.2 provides the current energy performance of the whole built environment at the city level; however, the methodology should also be able to support decision making about future energy planning 26 . In this context, a further effort was made to perform an analysis of different future scenarios using a deterministic method.…”
Section: Deterministic Heating Energy Consumption Modelingmentioning
confidence: 99%